Case Report: Systemic Treatment and Serial Genomic Sequencing of Metastatic Prostate Adenocarcinoma Progressing to Small Cell Carcinoma - Lu, XiaoJun; Gao, Wenwen; Zhang, Yu; Wang, Tao; Gao, Hongliang; Chen, Qing; Shi, Xiaolei; Lian, Bijun; Zhang, Wenhui; Gao, Xu; Li, Jing (Frontiers in Oncology, 2021)
Small cell carcinoma (SCC)/neuroendocrine prostate cancer (NEPC) is a rare and highly aggressive subtype of prostate cancer associated with an AR(androgen receptor)-null phenotype and visceral metastases. This study presents a 44-year-old man originally diagnosed with metastatic hormone-sensitive prostatic adenocarcinoma. After 6-month androgen deprivation therapy (ADT) combined with docetaxel, the patient developed paraplegia. Laminectomy was performed, and a thoracic vertebral biopsy revealed neuroendocrine differentiation and mixed adenocarcinoma. The patient developed liver metastases and experienced stable disease for 4 months following etoposide combined with cisplatin and pembrolizumab. Seminal vesicle biopsy after chemotherapy revealed small-cell cancer. The prostate biopsy specimen also indicated pure SCC. We witnessed the dynamic evolution from pure adenocarcinoma to fully differentiated SCC, leading to obstruction and death. In addition, whole-exome sequencing was performed on both biopsy specimens of the thoracic vertebra at the beginning of castration resistance and that of seminal vesicle after multiple lines of treatment failure. Utilizing phylogenetic reconstruction, we observed that both samples shared a common ancestor clone harboring aberrations in the TP53, RB1, and NF2 genes. We also discovered that driver events in the private subclones of both samples, such as alterations in CDC27 and RUNX1, might have played a significant role in tumor progression or even neuroendocrine differentiation. Tumor biopsy and IHC assessment must be repeated at different stages of progression, because of intrapatient spatial and temporal heterogeneity of adenocarcinoma versus SCC/NEPC. Although, typical treatments including ADT, docetaxel, etoposide, cisplatin, and pembrolizumab provided temporary response, the patient still had a poor prognosis.